Jobs, training, and worker well-being - Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics ;, 2010)
This volume contains twelve cutting edge papers contributing new research to important issues concerning worker welfare. The research deals with earnings inequality, discrimination, the effects of migration, and economic policy. Answers to a number of policy related questions are given including: Why are jobs designed the way they are? Does seniority-based pay provide a sufficient motivation for workers? Do sex-segregated firms grow more quickly than firms more equally divided by gender? What policies are effective in combating discrimination? Why is relative rural urban income inequality so much greater in China than the US? How does migrating from one region to another affect one's child's schooling decisions? Do higher migration levels affect native worker wages?